La collection / Musée des arts contemporains de la Fédération Wallonie-Bruxelles - Musée des Arts Contemporains de la Communauté Française de Belgique (2007)
[Dt.:] Die belgische Zechenanlage und Idealstadt Grand Hornu aus dem frühen 19. Jahrhundert beherbergt heute u.a. ein Museum fur Moderne Kunst. Die Sammlung des Museums kann online recherchiert werden. - [Engl.:] Grand Hornu is a Belgian mining company, built beginning in 1821 in neo classicist style, was a complete town, with houses, offices and owner s villa. The Museum for Contemporary Art is a attached to the ruins. The collection is available online.